2000
DOI: 10.1128/iai.68.1.197-204.2000
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of CD4+Th1 Cells in Systemic Immunity Protective against Primary and Secondary Challenges withTrypanosoma cruzi

Abstract: In general, gamma interferon (IFN-␥)-producing CD4؉ Th1 cells are important for the immunological control of intracellular pathogens. We previously demonstrated an association between parasite-specific induction of IFN-␥ responses and resistance to the intracellular protozoan Trypanosoma cruzi. To investigate a potential causal relationship between Th1 responses and T. cruzi resistance, we studied the ability of Th1 cells to protect susceptible BALB/c mice against virulent parasite challenges. We developed imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
88
1
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 50 publications
8
88
1
6
Order By: Relevance
“…Using the Th1/Th2 cell transfer system, we demonstrate that initial priming of a Th1 response is required for control of T. cruzi infection. This conclusion is supported by the recent results of Hoft et al (48) demonstrating that immunization of mice under conditions that promote a Th1 response results in protection from challenge infection with T. cruzi. In addition, these results confirm and extend the findings from our laboratory that mice lacking the ability to produce Th2 responses (as a result of targeted knock-of the stat6 gene) develop highly efficient immune responses and less sever disease than wild-type mice (61).…”
Section: Discussionsupporting
confidence: 79%
“…Using the Th1/Th2 cell transfer system, we demonstrate that initial priming of a Th1 response is required for control of T. cruzi infection. This conclusion is supported by the recent results of Hoft et al (48) demonstrating that immunization of mice under conditions that promote a Th1 response results in protection from challenge infection with T. cruzi. In addition, these results confirm and extend the findings from our laboratory that mice lacking the ability to produce Th2 responses (as a result of targeted knock-of the stat6 gene) develop highly efficient immune responses and less sever disease than wild-type mice (61).…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, we found that neutrophils play opposite roles in these two strains of mice with respect to protection or exacerbation of T. cruzi infection, possibly through modulating the Th1/Th2 dichotomy in different directions. Our results may add to the understanding of the role of Th1/Th2 dichotomy for pathogenesis of T. cruzi infection, which has been regarded as more complicated than that in L. major infection [3,10].…”
Section: Introductionmentioning
confidence: 97%
“…Parasite-specific CD4 ϩ T cells inhibit T. cruzi replication in vitro (5) and confer protection against lethal challenge in vivo (6). Induction of T. cruzi-specific CD4 ϩ and CD8 ϩ T cells is a critical component of vaccine-induced immunity to T. cruzi (7)(8)(9).…”
mentioning
confidence: 99%